NET TREFFERS TEL - Otto, W. (Scientia Militaria - South African Journal of Military Studies, 2012)
In recent years historical writers in the United States have begun to question the accuracy of the patriotic mythology of the American soldiers' markmanship. Particular attention has been paid to the American Civil War and it is evident from, a study of the facts that troops on both sides were indifferent shots. A large proportion of the Federal soldiers was recruited from urban backgrounds and lacked any knowledge of fire-arms. Rifles thrown away at Gettysburg provide ample proof of the lack of expertise among thousands of troops of the Confederate armies and even some of the regiments of the western states made very poor showings at target practice. As in the case of the American frontiersman, the Republican burghers of the late nineteenth century have enjoyed a reputation of incredible ability with a rifle. Yet a comparison of ammunition expenditure and casualty lists in the Second Anglo-Boer War surely give pause for thought and there seems ample evidence to bring the truth of the sharpshooting tradition into question. Such myths are indeed hazardous, for they breed complacency in the present day, where a very real danger exists that the modern South African soldier will assume that he has inherited the ability of markmanship instead of realising that this is not an inborn characteristic but rather something achieved after long practice and great mental application.